RETRACTED ARTICLE: How do EFL in-service teachers reflect on their critical incidents? The case of Iranian teachers. Issue 4 (4th July 2021) - Molani, Haideh; Yousefi, Mohammad Hosssein; Rostami, Farzad
Statement of Retraction: We, the Editors and Publisher of the Journal of Reflective Practice: International and Multidisciplinary Perspectives, have retracted the following article: Haideh Molani, Mohammad Hosssein Yousefi & Farzad Rostami (April 2021). How do EFL in-service teachers reflect on their critical incidents? The case of Iranian teachers, Reflective Practice, 22(4), https://doi.org/10.1080/14623943.2021.1913578 Since publication, it has been brought to our attention that this article has substantial overlap, with the article(s) listed below: Mahmood Reza Atai and Hassan Nejadghanbar, (March 2016). Unpacking in-service EFL Teachers' Critical Incidents: The Case of Iran, RELC Journal, 47(1). Link: https://journals.sagepub.com/doi/10.1177/0033688216631177 Oliver McGarr and Orla McCormack, (July 2015). Counterfactual mutation of critical classroom incidents: implications for reflective practice in initial teacher education, European Journal of Teacher Education, 39(1), 36-52. Link: https://www.tandfonline.com/doi/abs/10.1080/02619768.2015.1066329?journalCode=cete20 Monique M.J. Engelbertink, Jordi Colomer, Kariene M. Woudt- Mittendorff, Ángel Alsina, Saskia M. Kelders, Sara Ayllón & Gerben J. Westerhof, (2021). The reflection level and the construction of professional identity of university students, Reflective Practice, 22(1), 73-85. Link: https://www.tandfonline.com/doi/pdf/10.1080/14623943.2020.1835632?needAccess=true As this represents a serious breach of publishing ethics and of warranties made by the author with respect to originality and provenance, we are retracting the article from the journal. The authors do not agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.